Glucometers for Patients with Type 2 Diabetes Mellitus: Are they helpful? - Andrew Thomas; Mohan T. Shenoy; K.T. Shenoy; Nirmal George (International Journal of Medical Students, 2021)
Background: The effectiveness of self-monitoring of blood glucose (SMBG) in type 2 diabetes mellitus (T2DM) patients is debated in the literature. We aimed at elucidating the association and patterns of complications between SMBG use and plasma glucose values.